High and intermediate grade ductal carcinoma in-situ of the breast: a comparison of pathologic features in core biopsies and excisions and an evaluation of core biopsy features that may predict a close or positive margin in the excision - Clement Nathan F; Fadare Oluwole; Ghofrani Mohiedean (BMC, 2009)
Abstract Low and high-grade ductal carcinoma in-situ (DCIS) are known to be highly disparate by a multitude of parameters, including progression potential, immunophenotype, gene expression profile and DNA ploidy. In this study, we analyzed a group of intermediate and high-grade DCIS cases to determine how well the core biopsy predicts the maximal pathology in the associated excisions, and to determine if there are any core biopsy morphologic features that may predict a close (≤ 0.2 cm) or positive margin in the subsequent excision. Forty-nine consecutive paired specimens [core biopsies with a maximal diagnosis of DCIS, and their corresponding excisions, which included 20 and 29 specimens from mastectomies and breast conserving surgeries respectively] were evaluated in detail. In 5 (10%) of 49 cases, no residual carcinoma was found in the excision. In another 4 cases, the changes were diagnostic only of atypical ductal hyperplasia. There were 4 and 3 respective cases of invasive and microinvasive carcinoma out of the 49 excision specimens, for an overall invasion frequency of 14%. In 28 cases where a sentinel lymph node evaluation was performed, only 1 was found to be positive. Among the 40 cases with at least residual DCIS in the excision, there were 5 cases in which comedo-pattern DCIS was present in the excision but not in the core biopsy, attributed to the lower maximal nuclear grade in the biopsy proliferation in 4 cases and the absence of central necrosis in the 5th. For the other main histologic patterns, in 8 (20%) of 40 cases, there were more patterns identified in the core biopsy than in the corresponding excision. For the other 32 cases, 100%, 66%, 50%, 33% and 25% of the number of histologic patterns in the excisions were captured in 35%, 5%, 17.5%, 15% and 7.5% of the preceding core biopsies respectively. Therefore, the core biopsy reflected at least half of the non-comedo histologic patterns in 77.5% of cases. In 6(15%) of the 40 cases, the maximum nuclear grade of the excision (grade 3) was higher than that seen in the core biopsy (grade 2). Overall, however, the maximum nuclear grade in the excision was significantly predicted by maximum nuclear grade in the core biopsy (p = 0.028), with a Phi of 0.347, indicating a moderately strong association. At a size threshold of 2.7 cm, there was no significant association between lesional size and core biopsy features. Furthermore, the clear margin width of the cases with lesional size ≤ 2.7 cm (mean 0.69 cm) was not significantly different (p = 0.4) from the cases with lesional size > 2.7 cm (mean 0.56 cm). Finally, among a variety of core biopsy features that were evaluated, including maximum nuclear grade, necrosis, cancerization of lobules, number of tissue cores with DCIS, number of DCIS ducts per tissue core, total DCIS ducts, or comedo-pattern, only necrosis was significantly associated with a positive or close (≤ 0.2 cm) margin on multivariate analysis (Phi of 0.350). It is concluded that a significant change [to invasive disease (14%) or to no residual disease (10%)] is seen in approximately 24% of excisions that follow a core biopsy diagnosis of intermediate or high-grade DCIS. Core biopsy features are of limited value in predicting a close or positive margin in these lesions.